Eﬀects of a Subchronic Intoxication with Cadmium in the Hippocampus of Rats Fed a Soybean-Based Diet - Plateo Pignatari, Maria Gabriela (2018)
Experimental and population studies have shown that sub chronic exposure tocadmium (Cd) causes severe toxic eﬀects in several organs including in the brain,but information on the eﬀects in the hippocampus (Hp) is rare. Soybean is animportant source of protein and isoﬂavones. Herein we hypothesized that a subchronic cadmium-intoxication throughout the drinking water can cause oxidative/inﬂammation changes and apoptosis in the Hp; and that a soybean-based diet(SBD) can modulate these eﬀects. To accomplish this goal, we fed 4 groups offemale Wistar-rats for 60 days as follows: casein-based diet + tap water (CBD);CBD + tap water with 15 ppm Cd (CBD + Cd); soybean-based diet + tap water(SBD); and SBD + tap water with 15 ppm Cd (SBD + Cd). After the treatment,molecular markers of oxidative stress, inﬂammation, and apoptosis were measuredin serum and Hp tissue. Compared to the Hp of CBD fed rats, the Hp of CBDCd showed an apoptotic profle (high p53 and high Bax / Bcl-2 ratio). However,an SBD caused a pro-apoptosis pattern, i.e, increased p53 and Bax expression,reduced Bcl-2 expression and increased Bax / Bcl-2 ratio. Regardless increasedantioxidant enzymes, Cd exposure in SBD fed rats had a synergistic eﬀect in lipidperoxidation and protein oxidation in the Hp. Taking together our data suggest thatan SBD and Cd-exposure have a synergistic eﬀect on oxidative stress/inﬂammationand apoptosis in Hp. Caution may be taken on using soybean as a source of proteinin patients exposed to Cd.